Potensi Interaksi Antar Obat dalam Peresepan Rawat Jalan Pasien Penyakit Jantung Akibat Hipertensi - Ilil Maidatuz Zulfa; Yessy Asli Rahmawati; Putri Febri Anggraini (Fakultas Farmasi Universitas Setia Budi, 2022)
Hypertension or high blood pressure have contributed to the occurrence of cardiovascular disease. One of its complication is the development of Hypertensive Heart Disease (HHD). HHD pharmacological treatments usually combine antihypertensive and other agents that lead to polypharmacy. The use of multiple medications or polypharmacy will increase the potential of drug-drug interactions (PDDIs) that affect the therapeutic effect and increase adverse events. This study was aimed to analyze the prevalence and predictor of the PDDIs among HHD patients prescriptions in order to prevent the adverse effects and optimalize the therapy management. A retrospective observational study was conducted on HHD outpatients prescriptions. Medscape Drug Interaction Checker application was used to identify PDDIs. The mechanism, severity, number of interaction per prescription and most common interaction pairs of PDDIs were documented. In addition, age, gender, and the number of drug prescribed were analyzed as predictors of PDDIs using logistic regression binomial test. A total of 100 HHD outpatients prescriptions was analyzed and 94 of them had PDDIs. Majority of prescriptions had 3-4 and >4 PDDIs (33.00% each). Total of PDDIs observed were 397 cases. Most of PDDIs happened in the pharmacodynamic phase (86.40%) and need to monitored closely (93.20%). The concomitant use of Candesartan and Bisoprolol was found to be the most commpon interaction pair (11,08%) that can lead to the raise of potassium serum levels. The result of predictors analysis showed that the higher number of drug prescribed the higher the risk of the occurrence of PDDIs respectively (p-value 0,005) which addition 1 drug item will increase the PDDIs 7,232 time higher. In conclusion, the higher number of drug prescribed the closer monitoring need for PDDIs. In addition, closely monitoring in the elevating of potassium serum levels and the symptoms of hyperkalemia are needed in the treatment of HHD outpatients